THESEUS: A techno-economic design, integration and downselection framework for energy storage. (15th May 2023) - Zantye, Manali S.; Gandhi, Akhilesh; Li, Mengdi; Arora, Akhil; Sengalani, Pavitra Senthamilselvan; Wang, Yifan; Vudata, Sai Pushpitha; Bhattacharyya, Debangsu; Hasan, M.M. Faruque
Abstract: Optimal selection of energy storage technologies is critical to ensure reliable integration of intermittent and often uncertain renewable energy in electricity grids. The consideration of a diverse set of energy storage technologies is required for a more sustainable deployment of energy storage. We present THESEUS (TecHno-Economic framework for Systematic Energy storage Utilization and downSelection), which is a comprehensive framework for the optimal selection, design and operation of energy storage systems. THESEUS includes rigorous models of major energy storage technologies at different maturity levels, such as thermal storage using phase-change materials or molten salt, cryogenic storage, mechanical storage in the form of compressed air and pumped hydro storage, chemical storage using hydrogen, and electrochemical storage in the form of lithium-ion, sodium sulfur and vanadium flow batteries. An illustrative case study on state-wide prospective energy storage shows that storage integration with fossil power plants could reduce the cost of meeting the grid energy demand by 20%, with mechanical storage as the best suited technology. Although high-temperature thermal storage has low storage efficiency, it is optimal for integration with renewable energy plants. In addition, Li-ion batteries are optimal for high ramping but low storage duration requirements. Such insights can enable the deployment of both existing and emerging energy storage technologies to facilitate a smooth transition to a clean energy future. Highlights: Development of a mathematical programming-based decision framework. Nine energy storage technologies embedded in the optimization framework. Techno-economic study for various power demand and renewable penetration conditions. Evaluation of a complex integrated system with storage and power plant dynamics. Comparison of emerging and mature energy storage technologies for clean energy.